Addressing serious juvenile violence: rRecommendations for policy and practice - Lane, Jodi (The Routledge international handbook of juvenile homicide, 2024)
Serious juvenile violence, including murder, became the key crime policy focus in the early 1990s when rates skyrocketed, and scholars warned of impending doom as the teenage population ballooned over the next decade. These scholars were wrong, but for years the resulting “get-tough” policies created long-term life consequences for juveniles involved in crime. This chapter discusses trends in the juvenile violence problem since then, before focusing on examples of policy and program efforts that do not work, those that can work, and making recommendations for how policymakers and practitioners might address juvenile violence moving forward.